Melatonin Prevents Brain Damage and Neurocognitive Impairment Induced by Plasmodium Berghei ANKA Infection in Murine Model of Cerebral Malaria - Ataide, Brenda Jaqueline de Azevedo; Kauffmann, Nayara; Mendes, Nívia de Souza Franco; Torres, Marjorie Lujan Marques; dos Anjos, Larissa Medeiros; Passos, Adelaide da Conceição Fonseca; de Moraes, Suellen Alessandra Soares; Batista, Evander de Jesus Oliveira; Herculano, Anderson Manoel; Oliveira, Karen Renata Herculano Matos (Frontiers in Cellular and Infection Microbiology, 2020)
Cerebral malaria is characterized by permanent cognitive impairments in Plasmodium-infected children. Antimalarial therapies show little effectiveness to avoid neurological deficits and brain tissue alterations elicited by severe malaria. Melatonin is a well recognized endogenous hormone involved in the control of brain functions and maintenance of blood-brain barrier integrity. The current study has evaluated the effect of melatonin on the histological alterations, blood-brain barrier leakage and neurocognitive impairments in mice developing cerebral malaria. Swiss mice infected with Plasmodium berghei ANKA strain was used as cerebral malaria model. Melatonin treatment (5mg/Kg and 10mg/Kg) was performed for four consecutive days after the infection and data have shown an increased survival rate in infected mice treated with melatonin. It was also observed that melatonin treatment blocked brain edema and prevented the breakdown of blood-brain barrier induced by the Plasmodium infection. Furthermore, hematoxylion-eosin staining revealed that melatonin mitigates the histological alterations in Plasmodium-infected animals. Melatonin was also able to prevent motor and cognitive impairments in infected mice. Taken together these results show for the first time that melatonin treatment prevents histological brain damages and neurocognitive alterations induced by cerebral malaria.